RANCANG BANGUN MODEL PERSEDIAAN DAN PEMILIHAN PEMASOK BAHAN BAKU KELAPA PARUT KERING DI PT. X - Siti Wardah; Tiena Gustina Amran; Parwadi Moengin (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2013)
PT. X is an integrated agro-industry coconut company. The main products produced aredesicated coconut from coconut grain with a shelf life of 7 days as raw materials. The companycurrently constrained in 30-40% expired stock at the warehouse and insufficient capacity of thewarehouse. Another problem is the supply of raw materials (desicated coconut) from suppliersaround 20-35% did not comply with the specifications of diameter ≥ 10 cm. Seeing these conditionsrequired the model design of inventory and supplier selection with a balance of shelf life andstorage capacity as well as alternative suppliers that capable to provide raw materials (desicatedcoconut) with a diameter ≥ 10 cm continually. The method used in the design of this model is thedevelopment of methods Economic Order Quantity (EOQP) and lagrange multiplier used for theeconomic lot size ordering and fulfillment warehouse storage capacity as well as methodsAnalitycal Hierarchy Process (AHP) for the selection of alternative suppliers that meet thespecifications of raw materials and economical ordering quantity lots. The results of the design ofthis model produced economically ordering lot size 300.000 coconuts with total inventory cost Rp.55,5 million and is the District 1 alternative suppliers. In accordance with the results of analysisand expert opinion that the study design was verified and valid models.